Libido enquanto elemento dramatúrgico na Phaedra de Sêneca - Camila Machado Reis (2020)
Dira Libido occurs in Phaedra as a resource that Seneca uses to gather affections and myths in his own way. In addition to nefas, furor and dolor (DUPONT, 1995), libido is also part of the dramatic resources, as it overflows Seneca's philosophical works and invades the tragedy of Phaedra in a peculiar way. We have translated the latin play into Portuguese and, based on the myth of Venus and the god Amor, we show its dramatic mechanism through excerpts from Seneca's philosophical work, with the aim of debating the word and exhibiting its mechanic in his dramaturgy. The present work aimed to contribute to the growing study of Seneca's dramaturgy and to reinforce the idea that he, among other things, was also a playwriter.